Long Non-Coding RNA LINC02747 Promotes the Proliferation of Clear Cell Renal Cell Carcinoma by Inhibiting miR-608 and Activating TFE3 - Ju, Xiang; Sun, Yangyang; Zhang, Feng; Wei, Xiaohui; Wang, Zhenguo; He, Xiaozhou (Frontiers in Oncology, 2020)
Abstract With the rapid development of biotechnology, long noncoding RNAs (lncRNAs) have exhibited good application prospects in the treatment of cancer, and they may become new treatment targets for cancer. This study aimed to explore lncRNAs in clear cell renal cell carcinoma (ccRCC). Differentially expressed lncRNAs in 54 pairs of ccRCC tissues and para-carcinoma tissues were analyzed in The Cancer Genome Atlas (TCGA), and the most significant lncRNAs were selected and verified in ccRCC tissues. We found that lncRNA LINC02747 was highly expressed in ccRCC (P<0.001) and was closely related to high TNM stage (P=0.006) and histological grade (P=0.004) and poor prognosis of patients (P<0.001). In vivo and in vitro experiments confirmed that LINC02747 could promote the proliferation of ccRCC cells. We also found that LINC02747 regulated the proliferation of RCC cells by adsorbing miR-608. Subsequent mechanistic research showed that miR-608 is downregulated in ccRCC (P<0.001), and overexpression of miR-608 inbibited the proliferation of RCC cells. Moreover, we found that TFE3 is a direct target gene of miR-608. MiR-608 regulated the proliferation of RCC cells by inhibiting TFE3. In conclusion, LINC02747 upregulates the expression of TFE3 by adsorbing miR-608, ultimately promoting the proliferation of ccRCC cells. The above findings indicate that LINC02747 acts as an oncogene in ccRCC and may be developed as a molecular marker for the diagnosis and prognosis of ccRCC. The LINC02747/miR-608/TFE3 pathway may become a new therapeutic target for ccRCC.